HEART VALVE DISEASE IN HYPERTHYROIDISM - Ade Yonata; Elza Febria Sari; Ika Prasetya (Fakultas Kedokteran Universitas Lampung, 2014)
The incidence of heart valve disease, especially mitral valve prolapse was first reported in hyperthyroid heart disease in 1981. Incidence of heart valve disease in the form of mitral regurgitation (MR) or tricuspid regurgitation (TR) reached 23% in patients with hyperthyroidism. 45 years old male with a chief complaint tightness, worsened since 1 week before entering the hospital. Since 2 years ago patient often feels palpitations and breathless if activity. About 5 months ago, patient was sweating a lot and tremble, increase in appetite but weight going down. Defecation 5-6 times a day. Visible and palpable lump in the neck diameter ±5 cm, soft, ned, part moves while swallowing. Laboratory showed free T4: 7.550, sensitive TSH: 0.010. Thoracic X-ray showed cardiomegaly with cardiac waist disappeared. ECG showed atrial fibrillation. Echocardiography showed LA + LV dilatation TAPSE 1.91, AR Moderate, Severe MR, AML prolapse in A2 and PML with EF: 62.7%. Ultrasonography showed Throid hyperthyroidism and thyroid scan results with the impression difusa bilateral goitre within crease of total thyroid uptake. Patients received digoxin, furosemide, PTU. Patients then performed MV Repair and AV Repair. The mechanism of valvular heart disease relationship in hyperthyroidism has not been completely understood. In patients with MPV, some studies have shown a high prevalence of HLA-Bw35. Increased production and secretion of acid polymukosakarida in Graves can accumulate all the heart valves, especially the mitral valve, causing the valve to thicken (myxomatous). MR in hyperthyroidism is said to be a consequence of mitral annulus dilatation due to the left ventricle is dilated. It has been reported also a gernline mutations of thyrotropin receptor gene in Chinese families with thyrotoxicosis and MVP. In hyperthyroid patients is important to explore the patient's cardiovascular condition, including the possibility of valve disorders. [JuKe Unila 2014; 4(8):225-232]